MARKETING STRATEGIES OF BMT IN EFFORTS TO INCREASE THE NUMBER OF CUSTOMERS: A SYSTEMATIC LITERATURE REVIEW - Nur Rizkiyah Ramadhani; Taufiqur Rahman (Jurnal Ilmiah Al-Tsarwah, 2025)
The proper marketing strategy planning is believed to encourage an increase in the number of customers by enhancing awareness, interest, and trust in BMT services. This study aims to identify, categorize, and analyze various marketing strategies implemented by BMT as discussed in academic literature, evaluate their effectiveness based on empirical evidence, and reveal the strengths and weaknesses of each strategy in increasing the number of customers, in order to identify research gaps that can serve as the foundation for this study. The method used is the Systematic Literature Review (SLR). Data were collected through Google Scholar using the Publish or Perish 8 application with the keywords “Marketing Strategy,” “Baitul Maal wat Tamwil (BMT),” and “Increasing the Number of Customers.” Through a systematic selection process, only 8 out of 169 articles were selected for further analysis. The results of the research questions indicate that BMT’s marketing strategies to increase the number of customers include the marketing mix, segmentation targeting and positioning (STP), digital marketing, customer relationship management (CRM), as well as personal selling and service excellence—all of which have proven to be effective, although each strategy has its own varying strengths and weaknesses